PENGARUH PENGGUNAAN SERBUK KACA SEBAGAI BAHAN PENGGANTI SEBAGIAN AGREGAT HALUS TERHADAP KUAT TEKAN BETON - Ode, Titin; Sahusilawane, Tonny; Marantika , Meyke (Journal Agregate, 2024)
Some of this bottle waste is directly disposed of into open land without any treatment. One alternative use for beer glass bottle waste is to make it a substitute for fine aggregate in concrete mixture, by processing it into pounded glass powder until it smoothly passes filter no. 12. The addition of glass powder by 0%, 2.5% and 5%. The concrete test specimen measures 15×15×15 cm and is planned according to the SNI method 03-2834- 2000. The test parameters carried out are in the form of a slump test and concrete compressive strength with a compressive strength standard of 200 Kg / cm² at a concrete age of 7 days. The results obtained in this study were the compressive strength of concrete the percentage of using 0% glass powder of 264.29 kg / cm2, 2.5% of 252.26 kg / cm2, and 5% of 192.80 kg / cm2. Slump test values percentage 0% 8 cm, 2.5% 8.8 cm and 5% 10.8 cm. So it can be concluded that the use of glass powder as a substitute for some fine aggregate against concrete compressive strength affects the quality of concrete compressive strength with a variation of 2.5% can increase the compressive strength of concrete greater than normal concrete. However, the more glass powder, the lower the compressive strength of the concrete obtained. While the use of glass powder as a substitute for some fine aggregates affects the value of the slump test, the more the percentage of the use of glass powder in the concrete mixture, the higher the slump value.